Adolescent Mental Health 2015
DOI: 10.1201/b18222-6
|View full text |Cite
|
Sign up to set email alerts
|

The Association between School Class Composition and Suicidal Ideation in Late Adolescence: Findings from the Young-HUNT 3 Study

Abstract: Background: Few studies have explored the association between social context and suicidal ideation using multilevel models. This study examines how suicidal ideation in adolescence is related to school class composition. Methods: Data were obtained from the Young-HUNT 3 study (2006)(2007)(2008), a population study of adolescents attending secondary school in the Norwegian county of Nord-Trøndelag. The final sample included 2923 adolescents distributed among 379 school classes in 13 schools. Multilevel logistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Young 15 found that the contribution of school in relation to suicidal attempts and behaviours is low (< 1%), but nevertheless important given the severity of the outcome. School classroom context was also examined in a multilevel analysis, 16 which found small variation was attributed to school classes after accounting for individuallevel risk factors, but suicidal ideation is significantly associated with school class composition with regard to student gender and parental education. Multilevel analysis is therefore considered in this study, including the grade within school and school-level random effects, to give an enriched picture of the complexity of suicidal ideation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Young 15 found that the contribution of school in relation to suicidal attempts and behaviours is low (< 1%), but nevertheless important given the severity of the outcome. School classroom context was also examined in a multilevel analysis, 16 which found small variation was attributed to school classes after accounting for individuallevel risk factors, but suicidal ideation is significantly associated with school class composition with regard to student gender and parental education. Multilevel analysis is therefore considered in this study, including the grade within school and school-level random effects, to give an enriched picture of the complexity of suicidal ideation.…”
mentioning
confidence: 99%
“…It has also been suggested that suicidal ideation could be more common within schools or classrooms because associating with suicidal people has been shown to "spread" suicidal thoughts to others. 15,16 According to a major psychological theory -the ecological-transactional model 15,17 social behaviours are also affected by ecological context, such as (in hierarchical order) neighbourhood, community, school, peer and family groups. Multilevel modelling allows us to explore the importance of social context by dividing the total variation into individuals and groups to be assessed separately.…”
mentioning
confidence: 99%